The half-time talk: A mixed-method examination of youth-elite football coaches` behaviours and team-management strategies - Raya-Castellano, P. E.; Reeves, M. J.; Cárdenas-Vélez, D.; Fradua, L.; McRobert, A. P. (International Journal of Sports Science & Coaching, 2023)
Football, unlike some other team sports, includes limited game interruptions for coaches to easily communicate with players and affect their performance. However, a reduced number of studies have explored how coaches attempt to influence players during half-time. This study examined football coaches` behaviours during half-time and their perceptions underpinning their talks` delivery. Five Spanish coaches (Mage = 32.2, SD = 8.8) working for a La Liga academy were systematically observed during half-time talks (n = 20) and participated in a semi-structured interview each. Half-time talks were coded using a modified version of the Coach Analysis and Intervention System, and semi-structured interviews were analysed following thematic analysis procedures. Instruction and feedback were the most employed behaviours for four coaches, with younger age-group coaches employing greater divergent questioning and in-talk player participation. Furthermore, data suggested that coaches conferred with their staff, before entering the changing room and rapidly progressed from divergent to convergent questions and feedback and instruction. The team's `level of play` was the most perceived relevant factor affecting the verbal and vocal strategies of coaches` messages, albeit the score gained importance for coaches of older age-groups. This study is pioneering, examining how coaches attempt to influence their players during half-time talks of competitive youth football.